PENGARUH NILAI LAPORAN KEUANGAN TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - neni triana; maisyuri; miswar (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2022)
The purpose of this study is to study the relationship between NPM, ROA, DER, and ATO with the Stock Prices in Manufacturing companies listed on the Indonesia Stock Exchange. The research objects of manufacturing companies reported on the Indonesia Stock Exchange for the period 2012-2016. The sample in this study is a manufacturing company that has the most complete financial statements in 2012-2016 which supports 22. The results of the study show that NPM, ROA, DER, and ATO jointly test the stock price. Partially NPM does not support stock prices. ROA has a positive and significant impact on stock prices. DER does not affect stock prices. ATO has a positive and significant impact on stock prices. Keywords: NPM, ROA, DER, ATO, Stock Price